Pertumbuhan Planlet Anggrek Dendrobium sp. pada Media Cacahan Kulit Kayu dan Larutan Rooting Starter Selama Aklimatisasi - Nurromadon, Bilham; Ropalia, Ropalia; Zasari, Maera (JURNAL AGROTROPIKA, 2024)
Orchid plantlets are expected to be able to adapt and grow under optimal conditions during the acclimatization period. Selecting appropriate planting media and providing proper nutrition is one of the efforts that can be made to increase the success of high growth of Dendrobium, sp orchid plantlets during the acclimatization period. The aim of this research was to identify the appropriate planting medium and concentration of rooting starter solution to support the growth of Dendrobium sp orchid plantlets during acclimatization. This research was carried out from March to July 2022 at the Bangka Belitung University Experiment and Research Garden. This study used a factorial randomized block plan. The first factor is the planting medium; (M1) pine bark, (M2) Paraserianthes falcataria bark, (M3) acacia bark, and (M4) fern. The second factor is the industrial growth concentration 20 ml/l (K0) and 10 ml/l (K1). The results showed that the acclimatization of Dendrobium sp orchid plantlets was successful as seen from the large growth in plantlet height and the emergence of new shoots. The treatment that produced the highest growth of Dendrobium sp orchid plantlets during the acclimatization period was fern media and the best rooting starter concentration was 20 ml/l. The combination that showed the highest growth in Dendrobium sp. orchid plantlets during the acclimatization period was fern media + 20 ml/rooting starter. Key words:   Dendrobium, tree bark, acacia bark, fern, rooting starter, Paraserianthes